SUSTAINABILITY-DISCLOSURES AND FINANCIAL PERFORMANCE: SHARIAH COMPLIANT VS NON-SHARIAH- COMPLIANT INDONESIAN FIRMS - Mudeer Ahmed Khattak; Mohsin Ali; Aman Khan Burki (Journal of Islamic Monetary Economics and Finance, 2020)
We investigate the impact of sustainability-performance disclosure (SPD) on firm performance on a cross industry sample of 71 firms over the period 2011-2018. We also compare the relationship between shariah compliant firms (SCFs) and non-shariah-compliant firms(NSCF). To control for possible issues of unobserved heterogeneity, endogeneity and autocorrelation, we use the system generalized method of moments approach. We found that disclosure of sustainability performance increases a firm’s financial performance. Firms which disclose information on their sustainability practices were found to have higher earnings on assets and equity, which clearly supports the argument of information asymmetry. In the comparison of shariah-compliant and non-shariah-compliant firms, it was found that SCFs are at an advantage by being shariah compliant and that disclosure of sustainability performance increases the financial performance of such firms, whereas for non- shariah-compliant firms, the impact was found to be negative. One of the main findings from the research is that while firms’ involvement in corporate sustainability activities is encouraged, they also need to disclose any related information to their stakeholders, general public to capitalise on this investment, in return for a good reputation and consider going shariah complaint. Our study further recommends that the management of firms in Indonesia should focus on shariah compliance and consider sustainability-practice and sustainability-performance disclosures with a positive mindset, recognising them as means of gaining an advantage rather than as an obligation.